Leveraging AI for sustainable public procurement: opportunities and challenges - Andhov, Marta; Darnall, Nicole; Andhov, Alexandra (Frontiers in Sustainability, 2025)
Even though sustainable public procurement is critical to achieving global climate goals, most public organizations struggle to implement it. While artificial intelligence holds promise for addressing these challenges, its use in the public sector remains limited and often confined to discrete stages of the procurement lifecycle. This paper critically examines artificial intelligence’s potential to support sustainable public procurement across the full procurement lifecycle—from defining needs and assessing markets to issuing tenders, evaluating suppliers, and refining practices. Further, we examine the limitations and challenges posed by artificial intelligence technology for public procurement managers, recognizing concerns related to transparency, fairness, governance, and the impacts of artificial intelligence-driven decisions on market competition. Drawing on numerous examples in the practice, our findings show that artificial intelligence can be a powerful bridge between high-level sustainability aspirations and practical implementation, offering procurement officials the ability to access, interpret, and apply vast amounts of sustainability information across the entire procurement lifecycle. Our results provide understanding necessary to leverage artificial intelligence toward advancing sustainability across the entire procurement lifecycle, while highlighting the need for transparent, data-rich systems and collaborative engagement among technical experts, procurement professionals, and compliance and sustainability specialists. This analysis offers actionable insights into how AI can transform sustainable public procurement from aspiration to operational reality, enabling the public sector to use its considerable purchasing power to contribute meaningfully to global climate action.